Concept of asnaf al-gharimin : application at Lembaga Zakat Selangor / Aina Nabila Asmuri. - Asmuri, Aina Nabila (2020)
Zakat is an obligation to all Muslims to pay for it. There have different types of zakat and the zakat will also be divided into eight groups of asnaf. The concepts and meanings of each asnaf are different according to zakat centre in all state. This is because each state has its own scholars and mufti. So this research is to analyze the concepts and meanings of asnaf al-gharimin according to Lembaga Zakat Selangor. The objectives this research is to explain the concept of asnaf al-gharimin based on the opinion of scholar, to identify the expansion of meaning asnaf al-gharimin based on states in Malaysia and to analyse the application of asnaf al-gharimin by LZS. The method used for this research is qualitative which is using interview and library research method. The interview session has been done to the Head of the Social Management and Welfare Division of the Distribution Operations of Asnaf and Senior Shariah Research Executive Distributed Corporate Strategy Division. Finding show that application of asnaf al gharimin according to LZS is to help solving money problems of the people who have an income less than RM 5 000 per month but have a burden to bear like debt.